Plants used in folk medicine: the potential of their hydromethanolic extracts against Candida species - Martins, Natália (2015)
Currently, opportunistic fungal infections are considered a serious problem regarding public health. Despite the advances towards the synthesis of new antifungal agents, an increasing incidence of drug-resistant microorganisms has been observed. In this sense, other alternatives are necessary. In the present work, the antifungal activity of extracts from ten different plants, commonly used in folk medicine, were evaluated against nineteen Candida strains, including C. albicans, C. glabrata, C. parapsilosis and C. tropicalis species. Although the majority of the extracts had no antimicrobial effect, Juglans regia extract was very effective, exerting an inhibitory effect against all the tested Candida strains, while Eucalyptus globulus was effective against seventeen of them. Pterospartum tridentatum and Rubus ulmifolius presented similar antifungal effects, being effective against six Candida strains. The diameter of halo ranged, respectively, between 9-14 mm and 9-21 mm to the mentioned plant extracts, and the MIC50 values evidenced mainly a fungistatic activity. Both extracts showed similar MIC50 values for C. albicans strains, while C. parapsilosis and C. glabrata were more sensible to E. globulus. Otherwise, all the C. tropicalis strains were more sensible to J. regia. Overall, hydromethanolic plant extracts could constitute promissory alternatives to the traditional antifungal agents.